2016
DOI: 10.1103/physreva.93.013832
|View full text |Cite
|
Sign up to set email alerts
|

Fresnel coefficients of a two-dimensional atomic crystal

Abstract: In general the experiments on the linear optical properties of a single-layer two-dimensional atomic crystal are interpreted by modeling it as a homogeneous slab with an effective thickness. Here I fit the most remarkable experiments in graphene optics by using the Fresnel coefficients, fixing both the surface susceptibility and the surface conductivity of graphene. It is shown that the Fresnel coefficients and the slab model are not equivalent. Experiments indicate that the Fresnel coefficients are able to si… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
138
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 129 publications
(145 citation statements)
references
References 28 publications
7
138
0
Order By: Relevance
“…[33] where the electromagnetic field due to an electric current is obtained in terms of dyadic Green ′ s functions represented as Sommerfeld integrals. We believe that this approach is particularly appropriate and, in our opinion, even superior to other alternatives where the graphene is modeled as a layer of certain thickness and with an effective refractive index since the latter case fails to explain some of the results in remarkable optical experiments [34].…”
Section: Introductionmentioning
confidence: 99%
“…[33] where the electromagnetic field due to an electric current is obtained in terms of dyadic Green ′ s functions represented as Sommerfeld integrals. We believe that this approach is particularly appropriate and, in our opinion, even superior to other alternatives where the graphene is modeled as a layer of certain thickness and with an effective refractive index since the latter case fails to explain some of the results in remarkable optical experiments [34].…”
Section: Introductionmentioning
confidence: 99%
“…But a model treating them as three dimensional (3D) slabs with a certain thickness fails to explain the overall experiments on linear light matter interaction (absorption for instance) [8]. Instead a model considering the 2D atomic crystal as part of the interface plus the right boundary conditions, turns out to be the successful approach to explain its linear optical properties [8].Nonlinear optical properties of single layer and few layer atomic crystals have been investigated recently and they exhibit an extremely rich variety of physical phenomena. Single-layer MoS 2 [10-13] and BN [12] are non centrosymmetric materials, while their bilayers and bulk counterparts are expected to exhibit inversion symmetry [11][12][13].…”
mentioning
confidence: 99%
“…The transverse shifts are plotted as a function of incident angles and the refractive index of substrate. For one-layer graphene at wavelength 633nm, the surface conductivity and the surface susceptibility values are chosen as 6.08 × 10 −5 Ω and χ pp = χ ss = 1.0 × 10 −9 m, respectively [11]. The large spatial shifts occurs near a certain angle [ Fig.…”
Section: Strong Spin-orbit Interactionmentioning
confidence: 99%
“…In general, the interpretation of reflection and refraction on the surface of 2D atomically thin crystals is treated as a homogeneous medium with an effective refractive index and an effective thickness [5][6][7][8][9][10]. Recently, it has been demonstrated that the Fresnel model based on the certain thickness and effective refractive index fails to explain the overall experiments on light-matter interaction [11][12][13]. However, the Fresnel model based on the zero-thickness interface can give a complete and convincing description of all the experimental observation.…”
Section: Introductionmentioning
confidence: 99%